The Relationship Between The Movements Of Capital Markets In Developed Economies And Their Emerging Market Counterparts In The Asian Pacific Region - LOO, CHOO HONG (2004)
This research revisits at the relationship between the movements of capital markets in developed economies and their emerging market counterparts in the Asian Pacific region using market indices of the American, British, Malaysian, Singaporean, Mainland Chinese, Hong Kong Special Administrative Region (SAR), Indian, Japanese and Australian markets for the periods 1997 to 2003.